PERAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI MADRASAH TSANAWIYAH NAHDATUL ULAMA DUSUN LAALA KECAMATAN HUAMUAL KABUPATEN SERAM BAGIAN BARAT (IAIN Ambon, 2023)
ABSTRACT: The role of the school principal is a process or step in organizing, managing, planning and mobilizing to achieve mutually determined goals. The aims of this research are (1) to determine the role of the principal in improving the quality of education at MTs NU Laala, Huamual District, West Seram Regency, (2) to determine the supporting and inhibiting factors for the role of the principal in improving the quality of education at MTs NU Laala. Research This method uses a qualitative approach with descriptive methods supported by data collection through observation, interviews and documentation. The sources of information in this research are: the school principal, three teaching staff, one educational staff and two learners (students). The interview answers are classified and categorized based on aspects of the problem dimensions, then analyzed and interpreted descriptively. The data analysis techniques in this research are: data reduction (data selection), data presentation, drawing conclusions.Based on the research results, in showing the results that have been carried out by the school principal, (a). The role of the school principal as an educator (b). The role of the principal as manager, planning, organizing, actuating, controlling (c). The role of the principal as an administrator (d). The role of the principal as supervisor (e). The role of the head as a motivator. Supporting factors and inhibiting factors in improving the quality of education at MTs NU Laala are: supporting factors (a). Have a mutual sense of responsibility and solidarity between school principals and teaching/educational staff in improving school quality. (b). Parents and the community also participate to support activities at the school, both internal school activities and external activities (c). School principals provide a way for teaching and educational staff to take part in educational training programs to develop their competencies. The inhibiting factor is (a). Lack of facilities and infrastructure (b). Lack of students (c). Lack of teaching staff and educational staff. The author's conclusion is that the school principal carries out his role as an educator, manager, administrator, supervisor, motivator quite well and correctly.